2021
DOI: 10.1111/1365-2664.14076
|View full text |Cite
|
Sign up to set email alerts
|

Changes in arthropod communities mediate the effects of landscape composition and farm management on pest control ecosystem services in organically managed strawberry crops

Abstract: 1. Landscape composition and local diversification practices such as polyculture, cover cropping and hedgerows may promote natural pest control by benefiting natural enemy communities on farms. Our study employs piecewise structural equation modelling (PSEM) to test causal hypotheses regarding the effects of landscape composition and local diversification practices on arthropod communities and pest control ecosystem services.2. We sampled 27 organic strawberry fields in California's Central Coast region in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 122 publications
0
6
0
Order By: Relevance
“…For example, Morandin et al (2014) demonstrated that weeds contain more pests (including Lygus ) and fewer natural enemies relative to those collected from native perennial hedgerows. Similarly, Lu et al (2022) found that woodland habitat increased natural enemy abundance in organic strawberry, which in turn increased the likelihood of predation on sentinel Lygus nymphs; interestingly, grassy (i.e., weedy) habitats did not have a significant positive or negative effect on either outcome. Thus, the thoughtful diversification of strawberry production systems, which includes habitats inside and outside of cultivated fields, is warranted.…”
Section: Discussionmentioning
confidence: 90%
“…For example, Morandin et al (2014) demonstrated that weeds contain more pests (including Lygus ) and fewer natural enemies relative to those collected from native perennial hedgerows. Similarly, Lu et al (2022) found that woodland habitat increased natural enemy abundance in organic strawberry, which in turn increased the likelihood of predation on sentinel Lygus nymphs; interestingly, grassy (i.e., weedy) habitats did not have a significant positive or negative effect on either outcome. Thus, the thoughtful diversification of strawberry production systems, which includes habitats inside and outside of cultivated fields, is warranted.…”
Section: Discussionmentioning
confidence: 90%
“…Although energy use has been suggested as a useful proxy for prey consumption (Perović et al, 2018), it has also been argued that an increase in body size and energy requirement can alter predator–prey dynamics by shifting prey preferences or increasing intraguild predation, which can even result in a net negative effect of a higher energy requirement on pest consumption (Rusch et al, 2015). Similar mechanisms may be at work when richness increases, which may stimulate egg predation through resource partitioning and facilitation, but can also negatively affect pest predation due to negative intraguild interactions (Lu et al, 2021). Additionally, predator richness and energy use might have been better predictors if predators were identified to species level instead of family level, but this was not feasible due to the high number of juvenile specimens in our samples.…”
Section: Discussionmentioning
confidence: 99%
“…apple cultivation, biological control, integrated pest management, landscape context, organic management, semi-natural benchmark, structural equation modelling of direct effects of both local management and landscape variables on pest abundance and crop damage (Flores-Gutierrez et al, 2020;Samnegård et al, 2019) as well as indirect, predator-mediated effects (Lu et al, 2021), or combinations of both (Flores-Gutierrez et al, 2020;González et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations